Are recovery stories helpful for women with eating disorders? A pilot study and commentary on future research - Lisa Dawson; Barbara Mullan; Stephen Touyz; Paul Rhodes (Journal of Eating Disorders, 2018)
Abstract Background Anecdotally it is well known that eating disorder memoirs are popular with people with anorexia nervosa and recovery stories are readily available online. However, no research to date has empirically explored whether such stories are helpful for current sufferers. The aim of the current pilot study was to explore the efficacy of recovery narratives as a means of improving motivation and self-efficacy and to qualitatively explore patient perspectives of such stories. Method Fifty-seven women with anorexia nervosa and subclinical anorexia nervosa participated in this online study. Participants were randomised to either receive recovery stories or to a wait-list control group. After completing baseline measures, participants read five stories about recovery, and completed post-intervention measures two weeks later. Results The quantitative results indicated that reading stories of recovery had no effect on motivation and self-efficacy over a two-week period. In contrast, the qualitative results showed that the stories generated thoughts about the possibility of recovery and the majority indicated they would recommend them to others. Conclusions This study adds to a growing body of research exploring the integration of voices of lived experience into treatment approaches. Future research should focus on 1) identifying for whom and at which stage of illness recovery stories might be helpful; 2) the mechanism via which they might operate; and 3) the most helpful way of presenting such stories.